PENGEMBANGAN BAHAN AJAR KIMIA RINTISAN SMA BERTARAF INTERNASIONAL KELAS XI MATERI LAJU REAKSI - Inova Putri Carera; I Wayan Dasna (LPPM Universitas Terbuka, 2012)
This study was aimed to develop teaching materials about chemical reaction rate which covered materials adapted to A-Level High School students of grade XI in Pioneer International Standard High School (RSMA-BI). The developmental research was adopting the instructional development model 4D which include four stages of development, namely define, design, develop, and disseminate. Instructional materials were written in English consist of seven topics titled: Reaction Rate Concept, The Exchange's Expressions, Rate Law and Reaction Order, Experimental Determination of a Rate Law, Reaction Mechanism, Theories of Reaction Rate, Factors Affecting Reaction Rate. Results of content validation from content experts obtained the average score of 3. 56 of 14 range of scores which means valid / good / decent. Test limited to high school students of RSBI obtained an average score of 3.35 (valid / good / decent). The results of the use of teaching materials obtained a score of 77.8 which is above the minimal passing grade (75). Therefore it can be concluded that the materials were feasible to be used in the classroom.Penelitian ini bertujuan untuk mengembangkan bahan ajar laju reaksi dengan cakupan materi yang disesuaikan dengan A-Level untuk siswa kelas XI Rintisan Sekolah Menengah Atas Bertaraf Internasional (RSMA-BI. Rancangan penelitian pengembangan mengadaptasi model pengembangan bahan ajar Model 4D yang meliputi empat tahap pengembangan, yaitu define, design, develop dan disseminate. Produk pengembangan adalah bahan ajar kimia RSMA-BI kelas XI materi laju reaksi yang ditulis dalam bahasa Inggris menggunakan pendekatan kontekstual. Bahan ajar terdiri atas empat bagian utama yaitu pendahuluan, materi, evaluasi dan penutup. Materi tersusun atas tujuh sub materi yaitu Reaction Rate Concept, The Rates Expressions, Rate Law and Reaction Order, Experimental Determination of a Rate Law, Reaction Mechanism, Theories of Reaction Rate, Factors Affecting Reaction Rate. Hasil validasi isi dari ahli materi diperoleh nilai rata-rata 3,56 dari rentang skor 1-4 dengan kriteria valid/baik/layak. Hasil uji terbatas pada siswa SMA RSBI diperoleh nilai rata-rata 3,35 dari rentang skor 1-4 dengan kriteria valid/baik/layak. Hasil uji penggunaan bahan ajar diperoleh skor sebesar 77,8. Skor ini diatas SKM (Skor Kelulusan Minimal) yaitu 75 sehingga dapat disimpulkan bahwa bahan ajar telah layak dan dapat digunakan dalam pembelajaran di kelas.